Visions of Utopia : Gauging the State of Utopian Thought through Data Analysis - Joel Ramos Faustino; Joana Pinela (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
The Great Utopians project consists of a collection of historical figures deemed so because their revolutionary actions have helped advance our world and improve millions of lives. It is managed by CETAPS (Centre for English, Translation, and Anglo-Portuguese Studies) and is open to all contributions. This is a data set that, after careful analysis, may give us some interesting insights into the field of utopian thought. This paper analyzes the 77 entries of the Great Utopians collection along the lines of gender, birthplace, historical period, and field of excellence, to derive conclusions on gender imbalances, underrepresentation of utopianism both in time and in space, and the pronouncement of specific fields in what contributors of the project consider to be utopian work. We start the analysis with some preconceived notions about the underrepresentation of women and non-Europeans in the database. With this in mind, we review relevant literature on women's historical disenfranchisement, Eurocentrism's historical origins, and the complex definition of utopia. Afterwards, we describe the method of constructing the database and creating visual outputs for further data analysis. Then, we meticulously describe our findings when analyzing proportions of gender, birthplace, historical period, and field. Finally, we discuss these findings critically, considering our initial notions and detailing data that presented us with new and unexpected conclusions.